From existential uncertainty to a new mindset promoting recovery: Exploring the development of uncertainty experience in women with vulvar neoplasia - A qualitative longitudinal study - Jasmin Eppel-Meichlinger; Hanna Mayer; Enikö Steiner; Andrea Kobleder (BMC, 2024)
Abstract Background Women with vulvar neoplasia continue to experience uncertainty up to six months post-surgery. Uncertainty in illness is considered a significant psychosocial stressor, that negatively influences symptom distress, self-management strategies and quality of life. According to the Reconceptualized Uncertainty in Illness Theory, the appraisal of uncertainty changes positively over time in chronic illness. We aimed at exploring whether and how the experience of uncertainty develops in women with vulvar neoplasia. Methods We selected a purposive sample of seven women diagnosed with vulvar neoplasia in four Swiss and one Austrian women's clinic. By means of a qualitative longitudinal study, we conducted 30 individual interviews at five points of time during one year after diagnosis. We applied Saldaña's analytical questions for longitudinal qualitative research. Results First, participants experienced uncertainty as an existential threat, then an inherent part of their illness, and finally a certainty. Women initially associated the existential threat with a high risk for suffering from severe health deteriorations. Participants that could reduce their individually assessed risk by adopting health promoting behaviors, accepted the remaining uncertainty. From now on they reframed uncertainty into a certainty. This new mindset was based on a belief of promoting recovery and reducing the risk of recurrence. Conclusions The long-lasting and oscillating nature of uncertainty should receive attention in supportive oncology care. Uncertainty concerning existential issues is of special importance since it can inhibit a positive development of uncertainty experience.